PERAN FILSAFAT ILMU DALAM MENINGKATKAN KUALITAS PENELITIAN MANAJEMEN: PENDEKATAN EPISTEMOLOGI, ONTOLOGI, DAN AKSIOLOGI - Rahmat Hidayat; Ahmad Afandi; Marupa Siregar; Siti Mujiatun (JURNAL LENTERA BISNIS, 2024)
Philosophy of science is an important foundation in the development and preparation of scientific work, including in the field of management science. This article aims to analyze the application of the principles of philosophy of science, namely epistemology, ontology, and axiology, in management research through a literature review. The findings show that epistemology provides guidance for validity and data collection methods, ontology helps in understanding the nature of organizational reality, and axiology ensures that research is ethical and makes significant practical contributions. In addition, the study identified methodological approaches often used in management research, including positivism, post-positivism, and mixed methods, demonstrating the relevance of scholarly paradigms in understanding organizational complexity. Implications of the findings include contributing to the development of new paradigms in management science and providing practical guidance for structuring more valid, relevant, and ethically responsible research. The article's conclusion asserts that philosophy of science not only builds theoretical foundations but also strengthens the quality of management research, enabling the development of scholarly work that is meaningful to both the academic community and organizational practice. Recommendations are given for integrating philosophy of science in research education and training to enhance the relevance and impact of future research outcomes.